Tea Grounds and Coffee Grounds Support Sustainable Growth of Mustard Plants - Darwis; Yusran; Asrijal; Asia Arifin; Marufah (Postgraduate, University of Mataram, 2025)
The concept of organic farming is an effort to maintain optimal levels of environmentally friendly production. Therefore, this research aims to determine the effect of adding tea dregs and coffee dregs to compost media alone or mixed as additional nutrients on the growth of mustard greens (Brassica juncea L.). This research used a Completely Randomized Design (CRD) consisting of 4 treatments with 3 replications, namely compost without tea dregs and coffee dregs as control (P0). The research data were analyzed using Analysis of Variance (ANOVA) and Least Significant Difference Test (LSD) at a significance level of 5%. The results of the research obtained were that giving tea dregs and coffee dregs to the mustard plant planting medium obtained positive results. Single application of tea dregs had a significant effect on plant height (9.80 cm) and number of leaves (7.5). The treatment with tea dregs also had a significantly different effect from the control and other treatments. Meanwhile, coffee grounds alone contributed to a plant height of 7.1 cm and a number of leaves of 3.75, where the results obtained were not significantly different from the control and other treatments. However, overall, both single and mixed treatments had no significant effect on plant root length. The results of the ANOVA analysis for growth with the mustard plant height parameter obtained a value of Fcount of 4.496 > Ftable, namely 3.49, the parameter number of leaf blades Fcount 8.757 > Ftable, namely 3.49, and the root length parameter Fcount 0.367 < Ftable 3.49.